Effects of Bdellovibrio bacteriovorus HD100 on experimental periodontitis in rats. (10th December 2022) - Silva, Pedro Henrique Felix; Oliveira, Luiz Fernando Ferreira; Cardoso, Renata Silva; Santana, Sandro Isaias; Casarin, Renato Correa; Ervolino, Edilson; Salvador, Sergio Luiz; Palioto, Daniela Bazan; Furlaneto, Flávia Aparecida Chaves; Messora, Michel Reis
Abstract: Aim: The aim of this study was to evaluate the effects of Bdellovibrio bacteriovorus HD100 on experimental periodontitis (EP) in rats. Methods: Thirty‐two rats were divided into four groups: control, C‐HD100 ( B. bacteriovorus ), EP, and EP‐HD100. On day 0, EP was induced by the placement of cotton ligatures around the mandibular first molars (MFMs) in the EP and EP‐HD100 groups. In the C‐HD100 and EP‐HD100 groups, suspensions containing 1 × 10 9  PUF/ml of B. bacteriovorus HD100 were topically administered to the subgingival region of MFMs on days 0, 3, and 7. Animals were euthanized on day 14. Morphometrics analyses were performed in hemimandibles. The levels of tumor necrosis factor alpha (TNF‐α), interleukin (IL)‐6, monocyte chemoattractant protein (MCP)‐1, IL‐10, IL‐1β, transforming growth factor beta (TGF‐β), macrophage colony‐stimulating factor (M‐CSF) and regulated on activation and normal T cell expressed and secreted (RANTES) were determined by enzymatic immunoassays in gingival tissues. Beta defensin (BD)‐1, BD‐2, and BD‐3, Toll‐like receptors (TLR)‐2 and TLR‐4, and a cluster of differentiation (CD)‐4, CD‐8 and CD‐57 were analyzed by immunohistochemistry in hemimandibles. Data were statistically analyzed. Results: The EP group showed greater alveolar bone loss than EP‐HD100 ( p  < .05). The EP‐HD100 group showed higher levels of MCP‐1, RANTES, IL‐10, and TGF‐β, lower levels of TNF‐α than the EP group ( p  < .05). No differences were observed in IL‐1β, IL‐6, and M‐CSF levels between EP and EP‐HD100 groups. The C‐HD100 group had higher IL‐6, TNF‐α, RANTES, and MCP‐1 levels than the control group ( p  < .05). Regarding BD, the EP‐HD100 group showed a larger immunolabeling pattern for BD‐1, BD‐2, and BD‐3 than the EP group ( p  < .05). No significant differences in the immunolabeling pattern were observed for TLR‐2, TLR‐4, CD‐4, CD‐8, and CD‐57 between EP and EP‐HD100 groups. Conclusion: The topical use of B. bacteriovorus HD100 reduces alveolar bone loss, increases expression of BD, and modulates the cytokines levels on periodontal tissues in rats with EP.